Pemberian Buku Saku Motivasi Keluarga dan Pasien terhadap Penurunan Sisa Makanan Pasien Rumah Sakit - Slamet Iskandar; Isti Suryani (POLTEKKES KEMENKES YOGYAKARTA, 2018)
The cause factor of malnutrition cases in hospitalized patients is the lack of nutrients intake. The leftovers is an important indicator in food arrangement in a hospital. One of the Dietitian duties in hospital is giving counseling and motivation to patients related with diet, so it is necessary to have communication media to the patient in the ward. The objectives of study to identify the in?uence of distributing the pocket book “Family and Diabetes Mellitus Patients' Motivation toward the decline of leftovers. The type of the research is quasi experimental with pre-post test with control group design. The research was conducted on July - November 2015 in wards at Panembahan Senopati District Hospital, Bantul and Kulon Progo District Hospital. The number of sample in control group and treatment group is 96 each. The research samples were patients who meet the inclusion and exclusion criteria. The data analysis was done by using both univariate and bivariat analysis. Bivariat analysis used t-test or Mann Whitney U-Test. The leftovers from the control and treatment respondents at beginning of the research were similar. The leftovers from the control and treatment respondents at the end of the research were different. Based on the result of t-test of the respondents' leftovers at the beginning and the end of the research in the control group were the same, but based on the t-test of the respondents' leftovers at the beginning and the end of the research in the treatment group were different. In the other hand, the average of the decrease of patients' leftovers in the control and treatment is different. The leftovers decline in the treatment group is more than the control group. The distribution of pocket book “Family and Diabetes Mellitus Patients' Motivation is able to decrease the leftovers from the hospitalized patients.